Nora Prentiss [videorecording (DVD)] - Sherman, Vincent; Sheridan, Ann, 1915-1967; Smith, Kent, 1907-1985; Bennett, Bruce, 1906-2007; Alda, Robert (Archive collection., 2009)
A respected doctor fakes his death, deserts his family, throws away his career and drives himself to the edge of madness, all for the love of saloon singer Nora Prentiss.